Pelatihan Qira’ah Al-Sab’ah di Masjid Jami’ Darussholah Pakong Modung Bangkalan - Umar Zakka; Islamiyah Islamiyah; Ahmad Bahruddin (Universitas 45 Surabaya, 2023)
Qira'ah Al-Sab'ah training at the Jami' Darussholah Pakong Modung Bangkalan Mosque. The problem raised in this community service activity is related to the ability to read the Qur'an with Qiraah Sab'ah which is very important from the da'wah of Muslims, so learning about how to read the Koran with Qiraah Sab'ah must be conveyed with intense and easily understood by the jama'ah (local language allowed). To find alternative solutions to the above, a Qira'ah Al-Sab'ah training was held at the Jami' Darussholah Pakong Modung Bangkalan Mosque. The objectives of this PkM activity are: 1) Relating to the problem of the ability to recite the Qur'an for Pakong Village youth for the continuation of their studies. 2) Relating to the problematic knowledge of the theory of reciting the Koran in the Pakong village community. 3) Relating to the urgency of the ability to read the Koran. 4) Relates to the urgency of the ability to understand the theories of reciting the Koran and its application. 5) Relating to the use, direction and maximization of the potential for reading the Koran in the Pakong village community. Based on the agenda for the qira'ah al-Sab'ah training activities on Thursday night. Can provide knowledge and increase their ability to read the Koran, so that automatically their knowledge of reading the Koran will increase and be insightful.